Analysis of Na+ concentration patterns in trophectoderm cells of mouse blastocysts using a dual-wavelength electrolyte indicator - Ayaka Fujishima; Kazumasa Takahashi; Mayumi Goto; Akiko Fujishima; Takeo Hirakawa; Takuya Iwasawa; Hiromitsu Shirasawa; Yukiyo Kumazawa; Yukihiro Terada (PLoS ONE, 2025)
The developmental process of the mammalian blastocyst involves the intricate interplay of cellular and molecular mechanisms, including electrolyte dynamics within the trophectoderm (TE). We hypothesized that sodium (Na+) is actively transported from the TE into the blastocyst cavity, driving water influx and promoting blastocyst expansion. In this study, we investigated the dynamics of Na+ concentration in the TE of mouse embryos using sodium-binding benzofuran isophthalate (SBFI), a dual-wavelength Na+-sensitive fluorescent indicator. Observations revealed three distinct patterns of Na+ dynamics, each correlating with variations in blastocyst cross-sectional area and developmental outcomes. Embryos exhibiting an initial decrease followed by stabilization of Na+ concentration (Group A) demonstrated the highest rates of hatching, suggesting a relationship between Na+ flux and successful embryonic development. In contrast, embryos with transient increases (Group B) displayed reduced hatching rates and developmental progression. Further, the inhibition of Na+/K+-ATPase activity disrupted Na+ flux and blastocyst cavity expansion, emphasizing its critical role in blastocyst formation. This study highlights the potential of dual-wavelength imaging for elucidating electrolyte dynamics in preimplantation embryos and its implications for optimizing embryo culture systems in reproductive medicine.